Pengaruh Kualitas Pelayanan Harga dan Lokasi Terhadap Kepuasan Konsumen Pada Laundry di Kelurahan Banjar Tegal - Luh Putu Rian Mesiyani; I Nyoman Sujana (Ekuitas: Jurnal Pendidikan Ekonomi, 2025)
This study aims to analyze the effect of service quality, price, and location on consumer satisfaction in laundry businesses in Banjar Tegal Village, both partially and simultaneously. This study uses a quantitative approach with a causal research type. The population in this study were consumers who had used laundry services in Banjar Tegal Village, totaling 2,830 residents. The sampling technique used was accidental sampling, with a sample size of 191 respondents. The type of data used is quantitative, with data sources coming from primary and secondary data. Data collection was carried out through questionnaires, documentation, and observation. To analyze the data, this study used multiple linear regression analysis techniques. Hypothesis testing was carried out partially using the t-test and simultaneously using the F-test. The results of the study showed that (1) service quality has a positive and significant influence on consumer satisfaction at the laundry in Banjar Tegal Village, (2) price has a positive and significant influence on consumer satisfaction at the laundry in Banjar Tegal Village, (3) location has a positive and significant influence on consumer satisfaction at the laundry in Banjar Tegal Village, and (4) Simultaneously, service quality, price, and location together have a positive and significant influence on consumer satisfaction at the laundry in Banjar Tegal Village.